INVESTIGATION OF ANTHRAQUINONE CONTENTS, DNA CLEAVAGE, DNA BINDING, CYTOTOXIC AND ANTIOXIDANT ACTIVITIES OF XANTHORIA PARIETINA SAMPLES - GÜLER, Nilgün; KILIÇKAYA SELVİ, Emine (Studia Universitatis Babeș-Bolyai Chemia, 2025)
In this study, Xanthoria parietina samples were collected from different regions of Türkiye like Yozgat (Xp3), Izmit (Xp14), and Kütahya (Xp20). Anthracenedione, anthraquinone (parietin) contents of the lichens were determined quantitatively by GC-MS and spectrophotometric methods. The interaction of lichen extracts with pBR322 DNA and CT-DNA was examined by performing an agarose gel electrophoresis method. The cell proliferative activities of Xanthoria parietina samples were tested against the colon cancer cell line (DLD-1) by MTT assay. As a results of the GC-MS and spectrophotometric analysis, the highest and the lowest parietin contents were found for Xp20 and Xp14 extracts, respectively. These results were supported by those of the DNA cleavage, binding, and toxicity studies. The Xp14 sample can be considered as a drug that could be a new approach to cancer treatment, as it has the lowest polyaromatic hydrocarbon content and is not toxic for the cell.